2002
DOI: 10.1086/341290
|View full text |Cite
|
Sign up to set email alerts
|

A Global Perspective on Genetic Variation at the ADH Genes Reveals Unusual Patterns of Linkage Disequilibrium and Diversity

Abstract: Variants of different Class I alcohol dehydrogenase (ADH) genes have been shown to be associated with an effect that is protective against alcoholism. Previous work from our laboratory has shown that the two sites showing the association are in linkage disequilibrium and has identified the ADH1B Arg47His site as causative, with the ADH1C Ile349Val site showing association only because of the disequilibrium. Here, we describe an initial study of the nature of linkage disequilibrium and genetic variation, in pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
222
1
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(254 citation statements)
references
References 41 publications
23
222
1
8
Order By: Relevance
“…[33][34][35][36][37][38][39] The general pattern found in the regions examined so far is a series of discrete tracts of low recombination, high LD and therefore with a reduced number of haplotypes, the so-called 'haplotype blocks' bounded by recombination hotspots. Haplotype block structure has been found to vary according to genomic region (due to genomic factors affecting its pattern) and also between different global populations (due to demographic factors), 33,36,[38][39][40][41][42][43][44] see Bertranpetit et al 45 for a review. In fact, the goal of the International HapMap Project (http://www.hapmap.org) is to develop a haplotype map of the human genome, the HapMap, which will describe the common patterns of human DNA sequence variation in four distinct human populations.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37][38][39] The general pattern found in the regions examined so far is a series of discrete tracts of low recombination, high LD and therefore with a reduced number of haplotypes, the so-called 'haplotype blocks' bounded by recombination hotspots. Haplotype block structure has been found to vary according to genomic region (due to genomic factors affecting its pattern) and also between different global populations (due to demographic factors), 33,36,[38][39][40][41][42][43][44] see Bertranpetit et al 45 for a review. In fact, the goal of the International HapMap Project (http://www.hapmap.org) is to develop a haplotype map of the human genome, the HapMap, which will describe the common patterns of human DNA sequence variation in four distinct human populations.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, little is known about the magnitude and extent of LD in humans except that it varies among loci studied and among populations (eg see Tishkoff et al, 11 Kidd KK et al, 12 Kidd JR et al, 13 Stephens et al, 14 Reich et al, 15 and Osier et al 16 ). LD can be evaluated by a variety of statistics 17,18 that are functions of the haplotype frequencies in the population.…”
Section: Introductionmentioning
confidence: 99%
“…Those haplotype frequencies can also provide information on evolutionary histories, beyond what can be learned from individual markers. 16,22 We are studying RET both in order to understand the evolutionary histories of normal allelic variation at this locus and as an example of a centromeric locus in a region of known reduced recombination. In this study, we examine the haplotype frequencies and LD relations of six RET polymorphisms ( Figure 1) in 32 populations distributed around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Pertinent to the Indian subcontinent, while Goedde et al (1992) reported 9.9% ADH2*2 allele in a heterogeneous sample of Indians, Osier et al (2002) reported 6.6% of ADH2*2 allele in the Kachari population of Assam. These studies therefore cannot reflect the predominant pattern of distribution of ADH genes in the Indian subcontinent, which is contiguous to China and certain other Asian countries where some of these alleles show not only strong association with alcoholism but also high frequency of certain ADH alleles.…”
Section: Introductionmentioning
confidence: 98%
“…This allele codes for a protein with substitution Arg47 to His and, consequently, results in higher enzymatic activity (Osier et al 2002;Whiteld 2002). ADH2 genotypes, particularly the presence of an ADH2*2 allele, is related to differences in alcoholdrinking behaviour.…”
Section: Introductionmentioning
confidence: 99%